ABC1 consensus conference - a german perspective - Thomssen, Christoph; Marschner, Norbert; Untch, Michael; Decker, Thomas; Hegewisch-Becker, Susanna; Jackisch, Christian; Janni, Wolfgang; Lück, Hans-Joachim; Minckwitz, Gunter von; Scharl, Anton; Schneeweiss, Andreas; Tesch, Hans; et al. (Breast care, 2012)
ABC1-consensus ; Metastatic breast cancer, diagnosis and staging, treatment ; Tumor markers ; Metastases, biopsy ; Chemotherapy ; Endocrine therapy ; Anti-HER2-targeted therapy ; Palliative care